The Relationship between Sustainability Reports, Firm Size, and Company Value: The Moderating Role of Profitability in Oil and Gas Issuers Listed on the Indonesia Stock Exchange from 2019 to 2023: Hubungan antara Laporan Keberlanjutan, Ukuran Perusahaan, dan Nilai Perusahaan: Peran Moderasi Keuntungan pada Emiten Minyak dan Gas yang Terdaftar di Bursa Efek Indonesia dari Tahun 2019 hingga 2023 - Megawati Megawati; Usep Syaipudin; Retno Yuni Nur Susilowati (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: The oil and gas sector in Indonesia holds a strategic economic role while simultaneously facing increasing environmental, social, and governance demands from regulators and investors. Specific Background: Listed oil and gas companies are required to disclose sustainability reports alongside maintaining financial performance amid commodity price volatility during the 2019–2023 period. Knowledge Gap: Prior empirical studies report inconsistent findings regarding the relationships between sustainability reporting, firm size, and firm value, as well as the moderating role of profitability, particularly within capital-intensive and environmentally sensitive sectors. Aims: This study examines the relationships between sustainability reporting and firm size with firm value, and analyzes profitability as a moderating variable among oil and gas companies listed on the Indonesia Stock Exchange. Results: Using panel data regression on 50 firm-year observations, the findings show that sustainability reporting and firm size are positively and significantly associated with firm value. Profitability demonstrates a direct positive association with firm value and moderates the relationships between sustainability reporting and firm size with firm value. Novelty: The study extends prior research by integrating firm size as an explanatory variable and profitability as a moderating factor within the specific context of Indonesian oil and gas listed firms over a recent multi-year period. Implications: The results highlight the relevance of sustainability disclosure, corporate scale, and financial performance in shaping market valuation, offering insights for corporate management, investors, and policymakers concerned with sustainable corporate strategies in the oil and gas industry. Highlights: Sustainability disclosure shows a significant positive association with corporate valuation. Corporate scale demonstrates a statistically significant relationship with market-based value measures. Financial performance strengthens the relationships between disclosure practices, corporate scale, and valuation. Keywords: Pressure, ESG, Profitability